PEMANFAATAN MINERAL LOKAL ZEOLIT ALAM TERHADAP PERILAKU LENTUR BALOK SELF-COMPACTING CONCRETE (SCC) - Syamsudin, Ristinah; Nuralinah, Devi; Arisandi, Sukarno Yudha (Jurnal Mahasiswa Jurusan Teknik Sipil, 2014)
Self-Compacting Concrete (SCC) is a technological innovation in the manufacture of concrete that does not require compaction process to occupy formwork and solidified itself. In this research the manufacture of SCC used to harness the potential of local natural zeolite material which has almost the same chemical compound with fly ash or silica fume. The research was conducted through the manufacture of test specimens in 3 variations SCC without natural zeolite and natural zeolite were added levels of 5%, 10%, and 15% of the weight of the cement used in the mix. Beam has a main reinforcement 2-Æ8. The performed test is filling ability test, compressive strength of concrete, and flexural strength of concrete. Filling ability of SCC was measured by the test method slump flow and V-funnel test. From flexural strength testing were obtained ultimate load and beam deflection curves. The obtained results are given of natural zeolite levels influence on the flexural strength beams. The higher levels of natural zeolites are increase the result of flexural strength, but is limited to 10% levels When compared with normal concrete beams the flexural strength beam SCC natural zeolite amounted to 132,74 kg/cm2 has a 6.49% percentage increase. This is because the SCC natural zeolite beams with levels 10% and 15% of natural zeolite have a plastic phase is longer so the load can be held to be more bigger in line with the ability of beam deformation. The increase percentage reaches 18.46% when compared with normal concrete beam. Keywords : Beams, flexural strength, deflection, SCC, natural zeolite.